The Impact of Self Efficacy on the Foot Care Behavior of Type 2 Diabetes Mellitus Patients in Indonesia - Nuh Huda; Tintin Sukartini; Nadya Wahyu Pratiwi (Universitas Airlangga, 2019)
Introduction: Diabetes mellitus (DM) often causes complications, one of which is diabetic foot ulcers (DFUs). One of the factors involved in preventing diabetic foot injuries is performing foot care behavior. To improve patient behavior in terms of performing foot care is to improve self-efficacy. The purpose of this study was to determine the effect of the self-efficacy of diabetes patients on foot care behavior.Methods: This study used a descriptive correlational design to reveal the correlative relationships between the variables with a sample of 106 respondents using probability sampling in the form of cluster random sampling. The data was collected using questionnaires, the foot care confidence scale (FCCS), and the foot care behavior scale for diabetes (FCBS for Diabetes). The independent variable of this study was the self-efficacy of DM sufferers and the dependent variable of this study was the behavior of foot care. The data analysis used the Spearman Rho correlation test (α=0.05).Results: Spearman Rho correlation test showed there to be a relationship between the self-efficacy of people with diabetes mellitus and foot care behavior p value = 0.001 (p<0.05), r= -0.542.Conclusion: The implication of this study is that a high self-efficacy in people with diabetes mellitus will improve the behavior related to foot care, thereby reducing the risk of behaviors that damage the feet.